Exposure to 1, 2-Dichloropropane Upregulates the Expression of Activation-Induced Cytidine Deaminase (AID) in Human Cholangiocytes Co-Cultured With Macrophages. (19th November 2018) - Zong, Cai; Kimura, Yusuke; Kinoshita, Kazuo; Takasu, Shigetada; Zhang, Xiao; Sakurai, Toshihiro; Sekido, Yoshitaka; Ichihara, Sahoko; Endo, Ginji; Ichihara, Gaku
Abstract: 1, 2-dichloropropane (1, 2-DCP) was reclassified recently by IARC as a Group 1 carcinogen based on epidemiological studies on an outbreak of cholangiocarcinoma in offset-printing workers exposed to 1, 2-DCP in Japan. However, the underlying mechanism of 1, 2-DCP-induced cholangiocarcinoma remains obscure. A previous whole-genome mutation analysis of cholangiocarcinoma of 4 cases exposed to 1, 2-DCP suggested the involvement of activation-induced cytidine deaminase (AID), based on specific signatures of mutation patterns. The objective of the present study is to determine whether exposure to 1, 2-DCP induces expression of AID in human cholangiocytes. Human MMNK-1 cholangiocytes, differentiated THP-1 macrophages, and co-cultures of MMNK-1/THP-1 cells were exposed to 1, 2-DCP at different concentrations and time intervals. The mRNA expression levels of AID and related genes were quantified by real-time PCR. Protein expression was measured by immunostaining. Alkaline Comet assay was performed to examine DNA damage. The results showed that 1, 2-DCP alone did not change AID expression in MMNK-1 cholangiocytes. 1, 2-DCP significantly increased pro-inflammatory cytokine TNF-α expression in THP-1 macrophages. TNF-α treatment upregulated expression of AID, NF-κB, and IκB in MMNK-1 cholangiocytes. SN50, a NF-κB inhibitor, significantly downregulated TNF-α-induced AID expression, suggesting the involvement of NF-κB pathway in TNF-α-induced AID expression. Exposure to 1, 2-DCP significantly increased AID expression in MMNK-1 cholangiocytes co-cultured with THP-1 macrophages. Comet assay showed that 1, 2-DCP-induced DNA damage in MMNK-1 cholangiocytes, as indicated by increased tail DNA% and tail moment, was enhanced when co-cultured with macrophages. The results suggest that inflammatory response of macrophages and consequent aberrant AID expression or DNA damage in the cholangiocytes underlie the mechanism of 1, 2-DCP-induced cholangiocarcinoma in humans.